Cultural tourism to “contextualized tourism” a tourism different from the current tourism model in Mozambique: - Choe, Joao Francisco de Carvalho (2023)
The objet of study of this research is the set of actions, programs and strategies for implementing tourism in Mozambique. The discourses related to this sector, of recognized importance in terms of contribution to the Mozambican economy, when compared with the statistical data produced, reveal some disparity between what is defended as tourism revenue and what becomes palpable in terms of gains to from the development of tourist activity. One of the dominant reflections in the research at hand and around the planning, which seldom takes into account the real conditions of the places on which it is thought to implement some type of tourist activity. The most salient aspect of this observation concerns the poor quality or even the lack of infrastructure capable of ensuring competitive tourism and, therefore, a guarantee of economic development. The tourist facilities, the content of tourist information disclosed, the quality of transport, accommodation, catering and similar services greatly compromise the implementation of a more successful tourism that in fact contributes with visible and economically sustainable income. That is why we defend that for the full development of tourism in Mozambique it will only be possible if tourist development programs and strategies are designed that take into account the solution of local problems using local resources, a process in which collaborative action must be taken into account. and integration of different actors.